Copepod Diversity and Zooplankton Community Structure in a Coastal Special Area of Conservation (La Palma Island, Atlantic Ocean) - Adrián Torres-Martínez; Inma Herrera (Journal of Marine Science and Engineering)
This study presents the first species-level assessment of zooplankton communities within a designated Special Area of Conservation (SAC, ES7020122) in the coastal waters of an oceanic island in the Atlantic Ocean, conducted in a previously under-sampled protected coastal region. Copepods emerged as the predominant taxa, offering key insights into early-stage community structure and potential indicators of ecological dynamics in marine ecosystems. Zooplankton biomass and abundance were primarily driven by organisms in the 200–500 µm size fraction, with spatial variation observed across latitudinal transects. A total of 44 copepods species were identified, including dominant genera (Oncaea, Oithona, and Clausocalanus) characteristic of subtropical Atlantic ecosystems. Several indicator species (e.g., Candacia ethiopica and Oncaea scottodicarloi) showed spatial patterns. While no direct impacts from the recent 2021 volcanic eruption were detected, the dominance of opportunistic copepods and the observed diversity suggest a potential adaptive response and resilience of the pelagic community to periodic geological disturbances. These results provide a valuable ecological baseline for future long-term monitoring under the Marine Strategy Framework Directive and underscore the importance of copepods as indicators of coastal ecosystem structure and variability.